1997
DOI: 10.1128/jb.179.4.1280-1290.1997
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the fimA gene encoding bundle-forming fimbriae of the plant pathogen Xanthomonas campestris pv. vesicatoria

Abstract: The fimA gene of Xanthomonas campestris pv. vesicatoria was identified and characterized. A 20-mer degenerate oligonucleotide complementary to the N-terminal amino acid sequence of the purified 15.5-kDa fimbrillin was used to locate fimA on a 2.6-kb SalI fragment of the X. campestris pv. vesicatoria 3240 genome. The nucleotide sequence of a 1.4-kb fragment containing the fimA region revealed two open reading frames predicting highly homologous proteins FimA and FimB. FimA, which was composed of 136 amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 50 publications
2
55
0
5
Order By: Relevance
“…This was achieved in vitro by growth of the bacteria in hrp-inducing medium or by use of an hrpG* mutant which constitutively expresses the hrpG regulon. It is noteworthy to mention that no type IV fimbriae were observed under any of the growth conditions tested, although strain 85-10 was reported to carry a gene for type IV fimbriae (48). Altogether, these observations add another important plant pathogenic genus to the list of Hrp pilus-producing bacteria (32,49,59).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This was achieved in vitro by growth of the bacteria in hrp-inducing medium or by use of an hrpG* mutant which constitutively expresses the hrpG regulon. It is noteworthy to mention that no type IV fimbriae were observed under any of the growth conditions tested, although strain 85-10 was reported to carry a gene for type IV fimbriae (48). Altogether, these observations add another important plant pathogenic genus to the list of Hrp pilus-producing bacteria (32,49,59).…”
Section: Discussionmentioning
confidence: 77%
“…Pili were purified from strain 85E of X. campestris pv. vesicatoria by use of a deoxycholate-sucrose density gradient as described by Ojanen-Reuhs et al (48). Briefly, after mechanical detachment from the bacterial cells, cells were pelleted and the pili-containing supernatant was concentrated by precipitation with ammonium sulfate, dialyzed, and solubilized in buffer containing deoxycholate.…”
Section: Methodsmentioning
confidence: 99%
“…vesicatoria, the pilin structural gene was found by reverse genetics and subsequently inactivated. The nonpiliated mutant retained full virulence on tomato plants when tested under controlled conditions, but because Tfp promoted aggregation on leaf surfaces and increased resistance to killing by UV light the authors speculated that piliation might increase survival on leaf surfaces (Ojanen-Reuhs et al, 1997). Similarly, the Tfp of Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous Gram-negative bacteria, including some animal and plant pathogens, produce type IV pili (Tfp) (Ojanen-Reuhs et al, 1997 ;Roine et al, 1998 ;Strom & Lory, 1993 ;Su et al, 1999 ;van Doorn et al, 1994 ;. Depending on the organism, Tfp can be important for adhesion, aggregation, biofilm formation, horizontal gene transfer, multicellular development, pathogenesis and twitching motility (Fussenegger et al, 1997 ;Merz et al, 2000 ;Strom & Lory, 1993 ;.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are complex structures involving X. fastidiosa cells and an extracellular matrix. X. fastidiosa produces abundant multiple putative afimbrial adhesins, such as exopolysaccharide (EPS), lipopolysaccharide (LPS), and surface proteins, which contribute to the virulence of X. fastidiosa by attaching to the xylem wall in the plant and enhancing biofilm formation [33,[40][41][42][43]. Previously study showed that X. fastidiosa EPS was coded by a cluster of nine gum genes closely related to the xanthan gum operon of Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%